Cytokine profile of surgical patients with infective endocarditis - E. O. Kotova; A. S. Pisaryuk; A. V. Lokhonina; A. Y. Moiseeva; E. A. Domonova; T. A. Gusarova; J. I. Babukhina; P. V. Kakhktsyan; T. K. Fatkhudinov; Z. D. Kobalava (Рациональная фармакотерапия в кардиологии)
Aim. To study the cytokine profile of macrophages in valve tissues in operated patients with infective endocarditis (IE), its correlation with inflammatory markers for optimization of the assessment of IE activity.   Material and methods. There were prospectively included 25 adult patients with active IE (2015Duke criteria) and 24 patients with non-IE valvular heart disease admitted for cardiac surgery (2021-2022). Laboratory and instrumental examination was conducted, including pathogen verification, as well by means of Real-Time PCR in blood/tissues of resected valves, echocardiography, and neutrophil-to-lymphocyte ratio evaluation. Valvular tissues were analyzed for macrophage phenotypic characteristics using immunohistochemistry (IHC) and for pro- and anti-inflammatory cytokine gene expression via real-time PCR.   Results. IE patients had a high proportion of secondary IE due to degenerative heart defects (n = 10, 40.0 %) and left-sided localization of IE (n = 16, 64.0 %). IHC revealed a predominance of intact pro-inflammatory CD 86+ macrophages phenotype in patients without IE compared with patients with IE [0.054 (0.029-0.073) vs. 0.008 (0.0071-0.0096), p < 0.05]. There was no significant difference in the anti-inflammatory CD 206+ macrophages phenotype. In the group of operated patients with IE, Real-Time PCR revealed significant expression of IL-1β genes (Ме [IQR] 0.0037 [0.0005-0.0155] vs. 0.0002 [0.0001-0.0026], p < 0.05) and IL-6 (Ме [IQR] 0.0034 [0.0007-0.0167] vs. 0.0005 [0.0004-0.0038], p < 0.05) compared with patients without IE. There were no significant differences in anti-inflammatory cytokines. The level of cytokine gene expression by tissue macrophages, depending on the presence of embolic events, etiological affiliation to S. aureus, as well as hospital mortality and the combined endpoint (death from all causes or recurrence of IE in 6 months after surgery) did not differ between IE patients with or without events. IL-1β had the most favorable characteristics for assessing the activity of IE (IL-1β AUC 0.816 (p = 0.02)).   Conclusion. Increased macrophages destruction with excessive release of pro-inflammatory cytokines in the valve tissue determines the uncontrolled course of IE and the need for cardiac surgery. IL-1β has a high diagnostic value for determining the inflammation activity in operated patients with IE.